Community Empowerment in Processing of Household Organic Waste into Compost - Sri Wahyuni; Triastuti Sulistyaningsih; Siti Herlina Dewi; Nuril Huda; Mohammad Haris Baihaqi; Fika Maulydha Hardiyanti; Eka Siti Rinjani (Universitas Negeri Semarang, 2024)
Household waste, which is mostly in the form of food waste such as vegetables and fruits, is a source of waste accumulation. More than fifty percent of the waste accumulation in Banyudono village, Boyolali, Central Java is household waste. The accumulation of garbage causes environmental pollution problems that can result in a decrease in the quality of life of residents. Garbage accumulation occurs because residents only throw it into the surrounding environment or rely on garbage transport trucks to be disposed of in landfills. This is due to the lack of knowledge among of residents (the participant of the service activities) in waste processing. Proper waste management not only makes the environment clean and healthy, but also improves the community's economy through the creation of value-selling products. To overcome the partner's problem, namely the accumulation of waste, the service team provides solutions according to the partner's needs, namely the transfer of science and technology (IPTEK) to process household waste (organic) into organic fertilizer (compost). The transfer of science and technology to Banyudono Village residents take place in July 2023 and participants were given assistance to implement the science and technology to treat waste independently. The results were monitored 3 months later according to the known composting method. Composting is done using EM4 bioactivator so that the results can be harvested within 3 months of composting. Compost quality analysis is carried out after the compost is physical and chemical mature which confirmed by checking pH and levels of nitrogen, phosphorus, and potassium. The obtained compost was blackish with a smell like earth, and has a fine texture. The compost had a pH of 6.9 and the nitrogen, phosphorus, and potassium levels meets SNI standards. Through this activity, participants able to processing household waste independently.